Perspektif Pendidikan Islam Dalam Novel “Dan Damai Di Bumi!” Karya Karl May - Indriyani Ma’rifah (Faculty of Tarbiyah and Education State Islamic University (UIN) Sunan Kalijaga Yogyakarta, Indonesia, 2012)
Conflict and violence based on ethnicity, religion, race, and inter-groups (SARA) still become an inherent part of the historical life of Indonesian people. It is quite clear that the Islamic education has not been effective enough to instill values of peace. Therefore, the reconstruction and renewal of Islamic education should be done. It is necessary for us to begin with the reconstruction of the learning materials, and by using the novel as a medium. One of the novels that are loaded with the values of peace is “Dan Damai di Bumi!“ written by Karl May.